Explaining English Grammar - Yule G. George (Oxford Handbooks for Language Teachers)
This series is designed to provide a source of reference for both language teachers and teacher trainers. Each title is intended to serve both as a basis for courses and seminars, and as a longer-term reference text for the working teachers bookshelf Explaining English Grammar The aim or this book is to provide teachers with a fresh approach to thinking about English grammar. Each chapter focuses on a problematic area, for example 'Articles', 'Conditionals', and 'Direct and indirect speech'. First the basic grammatical form is described, and then the meaning distinctions conveyed by particular forms. The final section of each chapter shows how meaning can be shaped by context and communicative purpose. The book includes exercises, teaching ideas, and a glossary.